Notch sensitivity of short and 2D plain woven glass fibres reinforced with different polymer matrix composites - Elbadry, E.; Abdalla, G.; Aboraia, M.; Oraby, Elsayed (Sage Publications, 2017)
This research article investigated the notch sensitivity of two different glass fibre architectures, namely short and 2D plain-woven glass fibres reinforced with unsaturated polyester and epoxy matrix composites fabricated by the hand lay-up technique. This was carried out through open hole tension tests at different ratios of the specimen hole diameter to the specimen with three different values (0.1, 0.2, 0.5) compared to the unnotched specimen. The notch sensitivity of these composites was evaluated using the residual tensile strength by the application of Whitney-Nuismer Mathematical Model. The results showed that by using polyester matrix, the notch sensitivity of composites reinforced with plain-woven glass fibre is higher than that of short glass fibre at different D/W ratios. On the other hand, on testing epoxy matrixes, the notch sensitivity of composites reinforced with plain-woven glass fibre is lower than that of short glass fibre at different D/W ratios.